2000
DOI: 10.1523/jneurosci.20-16-06125.2000
|View full text |Cite
|
Sign up to set email alerts
|

FGF/FGFR-2(IIIb) Signaling Is Essential for Inner Ear Morphogenesis

Abstract: Interactions between FGF10 and the IIIb isoform of FGFR-2 appear to be crucial for the induction and growth of several organs, particularly those that involve budding morphogenesis. We determined their expression patterns in the inner ear and analyzed the inner ear phenotype of mice specifically deleted for the IIIb isoform of FGFR-2. FGF10 and FGFR-2(IIIb) mRNAs showed distinct, largely nonoverlapping expression patterns in the undifferentiated otic epithelium. Subsequently, FGF10 mRNA became confined to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
268
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(287 citation statements)
references
References 48 publications
19
268
0
Order By: Relevance
“…Fgfr2-DN (Celli et al, 1998), Fgfr2b Ϫ/Ϫ (De Moerlooze et al, 2000) and Fgfr2b Ϫ/ ϪLacZ (Revest et al, 2001) embryos exhibited dysgenesis in kidney formation; however, all Fgfr2 ⌬III/⌬III embryos do not have this organ (Li and Deng, unpublished observation). Inner ear defects of the Fgfr2 ⌬III/⌬III embryos also seem more severe than that of Fgfr2b Ϫ/Ϫ embryos (Pirvola et al, 2000;Li and Deng, unpublished observation). Apparently, the Fgfr2 ⌬III/⌬III embryo represents a more severe allele as it lacks both Fgfr2b and Fgfr2c isoforms.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Fgfr2-DN (Celli et al, 1998), Fgfr2b Ϫ/Ϫ (De Moerlooze et al, 2000) and Fgfr2b Ϫ/ ϪLacZ (Revest et al, 2001) embryos exhibited dysgenesis in kidney formation; however, all Fgfr2 ⌬III/⌬III embryos do not have this organ (Li and Deng, unpublished observation). Inner ear defects of the Fgfr2 ⌬III/⌬III embryos also seem more severe than that of Fgfr2b Ϫ/Ϫ embryos (Pirvola et al, 2000;Li and Deng, unpublished observation). Apparently, the Fgfr2 ⌬III/⌬III embryo represents a more severe allele as it lacks both Fgfr2b and Fgfr2c isoforms.…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, mouse embryos with a homozygous deletion of Fgfr2 Ig domain III (Fgfr2 ⌬lgIII/⌬lgIII ), which is shared by both FGFR2b and FGFR2c isoforms, died at E10.5 due to placental defects . Analysis of these mutant embryos revealed that FGFR2 is essential for induction and patterning of multiple organs, including limb, lung, inner ear, placenta, and skin (Arman et al, 1998(Arman et al, , 1999De Moerlooze et al, 2000;Pirvola et al, 2000;Revest et al, 2001;Xu et al, 1998). A similar observation was also made in embryos that overexpress a dominant-negative secreted Fgfr2 (Celli et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…At early stages of embryogenesis, Fgfr1, Fgfr2, and several FGFs, including FGF3, FGF8, FGF10, and FGF19, are critical for either the induction of the otic vesicle or the initial development of the sensory epithelium (Mansour et al, 1993;Ladher et al, 2000Ladher et al, , 2005Pirvola et al, 2000Pirvola et al, , 2002Phillips et al, 2001Phillips et al, , 2004Pauley et al, 2003;. At intermediate stages of development, FGF signaling is also important; tissuespecific deletion of Fgfr1 results in severe defects in the development of the auditory sensory epithelium apparently due to a severe reduction in the precursor cells that give rise to the organ of Corti.…”
Section: Introductionmentioning
confidence: 99%
“…Fibroblast growth factor (FGF) molecules have been identified as inductive signals for otic placode development in several vertebrate species (Represa et al, 1991;Mansour et al, 1993;De Moerlooze et al, 2000;Ohuchi et al, 2000;Pirvola et al, 2000Pirvola et al, , 2002Vendrell et al, 2000;Phillips et al, 2001;Leger and Brand, 2002;Maroon et al, 2002). Depletion of FGF3 prevents otic vesicle formation in tissue explants from chick (Represa et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ectopic otic vesicles can be induced by misexpression of FGF3 in chick (Vendrell et al, 2000) or implants of beads soaked with Fgf2 and Fgf3 in Xenopus posterior trunk ectoderm . Mice with null mutations for Fgf3, Fgf10, or FGF receptors Fgfr2IIIb or Fgfr1 exhibit defects in patterning and differentiation of the inner ear (Mansour et al, 1993;De Moerlooze et al, 2000;Ohuchi et al, 2000;Pirvola et al, 2000Pirvola et al, , 2002. In zebrafish, combined loss of function for fgf3 and fgf8 (fgf3/8) leads to the complete absence of the otic placodes in most embryos (Phillips et al, 2001;Leger and Brand, 2002;Maroon et al, 2002).…”
Section: Introductionmentioning
confidence: 99%